2012
DOI: 10.1121/1.3679390
|View full text |Cite
|
Sign up to set email alerts
|

Annoyance due to railway vibration at different times of the day

Abstract: The time of day when vibration occurs is considered as a factor influencing the human response to vibration. The aim of the present paper is to identify the times of day during which railway vibration causes the greatest annoyance, to measure the differences between annoyance responses for different time periods and to obtain estimates of the time of day penalties. This was achieved using data from case studies comprised of face-to-face interviews and internal vibration measurements (N=755). Results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Recently, Peris et al [41] proposed the index VDV b,den that, like the index L den in acoustics, aims to better represent, for vertical vibrations, the greater annoyance felt during the evening/night periods. This index was derived for railway traffic.…”
Section: Measuring and Evaluating Vibration Exposures 311 Measurinmentioning
confidence: 99%
“…Recently, Peris et al [41] proposed the index VDV b,den that, like the index L den in acoustics, aims to better represent, for vertical vibrations, the greater annoyance felt during the evening/night periods. This index was derived for railway traffic.…”
Section: Measuring and Evaluating Vibration Exposures 311 Measurinmentioning
confidence: 99%
“…In this work the mean proportion of freight traffic during day time hours (07:00 to 19:00) evening time hours (19:00 to 23:00) and night time hours (23:00 to 07:00) is 10.1, 18.2, and 21.5 %, respectively (SD ¼ 4.7, 12.0, 11.6). Peris et al (2012) demonstrated that annoyance due to equal levels of railway vibration exposure is greater during night time than during evening time, and greater during evening time than during day time. The fact that freight traffic is more prevalent during periods in which sensitivity to railway vibration is higher is therefore likely to affect the annoyance response to freight railway vibration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent evidence from exposure response curves [72,73] suggest that the standards (e.g., [74] or [48]) may underestimate the potential effects on sleep during evening and night hours". Unfortunately, the exposure response information in these studies used different vibration dose estimation parameters.…”
Section: Discussionmentioning
confidence: 99%